SANKSI HUKUM TERHADAP NOTARIS YANG MELANGGAR KEWAJIBAN DAN LARANGAN UNDANG-UNDANG JABATAN NOTARIS - ., Mardiyah; Setiabudhi, I Ketut Rai; Swardhana, Gde Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 2 No 1 (2017)DO - 10.24843/AC.2017.v02.i01.p10, 2017)
Law Number 2 of 2014 on Notary Function (UUJN) governs on Civil and Administrative sanctions to Notary violating obligations and prohibition as set forth in Article 16 and 17 of UUJN, however criminal sanction is not governed in the UUJN, therefore the application of criminal sanction itself has not been able to be imposed to a Notary violating the obligations and prohibitions of UUJN. And there is no arrangement to the mechanism of civil sanction imposition related to the cancellation of deed in the event of the authentic deed in the UUJN. Based on the background, the problems arising, namely, first How is the setting of legal sanctions against Notary violating Obligations and Prohibition  of  UUJN and second, what is the mechanism of handing down sanction (pursuant to the procedural law)  to the Notary  violating obligations and  prohibitions  UUJN how is the settlement mechanism of legal sanctions against Notary violating UUJN-P? This study is qualified as a normative legal research. The source of legal materials for this study was obtained from primary, secondary and tertiary legal materials. The results of this thesis are civil sanction is  governed in Article 16 paragraph (9 and 12), Article 41, Article 44 paragraph (5), Article 48  paragraph (3), Article 49 paragraph (4), Article 50 paragraph (5) and Article 51 paragraph (4) of UUJN. The administrative sanction is governed in Article 7 paragraph (2), Article 16 paragraph (11 and 13), Article 17 paragraph (2), Article 19 paragraph (4), Article 32 paragraph (4) Article 37 paragraph (2), Article 54 paragraph (2) and Article 65A of UUJN. Criminal sanctions are not governed, but a notary may be charged with criminal sanction pursuant to the provisions of Penal Code, providing that the act of the notary has complied with the formulation of breaches set forth in the UUJN, ethic codes and Penal Code. Second, the mechanism of application of civil sanction related to the cancellation of authentic deed into under hand deed should go through civil lawsuit process at general court lodged by the parties whose names are stipulated in the deed and suffer from damages as the effect of such deed. The mechanism of application of administrative sanctions to a notary should be directly imposed by the Supervisory Board, where the sanctions are gradually applied.  The mechanism of application of criminal sanction to a notary if proved to commit the criminal act, the Notary shall be penalized and generally Penal Code can be applied to the Notary pursuant to the principle of lex spcialist derogate legi generali interpreted in a contrario manner.